Green Synthesis of Silver Nanoparticles by Mentha Spicata Aqueous Leaf Extract - Najeh Hashim (Journal of Global Pharma Technology, 2018)
Silver nanoparticles which were synthesized by Mentha spicata aqueous leaf extract were characterized by UV-Visible Spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and Atomic Force Microscope. Antifungal activity tests were done against dermatophytes Microsporum canis, Trichophyton mentagrophytes, the result showed that silver nanoparticles was efficient in highest inhibition rate at 5 mg/ml. The antioxidant properties of the obtained biomaterial were assessed in vitro, using ABTS as free radical; the result suggests that silver nanoparticles present promising antioxidant activity; the effect of silver nanoparticles on human red blood cells hemolysis was investigated. Keywords: AgNps, Nanoparticles, Antifungal, Antioxidant.